The effects of novel electrical teat dipping on some mastitis parameters in dairy herds - Safak, Tarik; Risvanli, Ali; Yilmaz, Oznur; Yuksel, Burak; Saat, Nevzat; Tanyeri, Burak (Copernicus Gesellschaft Mbh, 2023)
Electrical teat dipping (ETD) is a novel, patented method developed by the authors to control mastitis in dairy cows. Here we evaluate the efficacy of ETD in reducing the incidence of clinical mastitis and bulk tank milk somatic cell count (BTMSCC) on three dairy farms over 6 months. ETD was applied for morning and evening milking on three farms, while conventional teat dipping (CTD) was applied on the other three farms. The number of animals and quarters with clinical mastitis and monthly BTMSCC measurements were recorded. We found that the incidence of clinical mastitis was lower on farms using ETD than those using CTD. However, the BTMSCC did not significantly change throughout the study. Based on these findings, we conclude that ETD effectively reduces mastitis rates on dairy farms.